V-shaped and circular ring defect on rectangular patch / Muhamad Azlan Anuar - Anuar, Muhamad Azlan (2013)
This thesis presents a V-shape defect on patch and circular ring defect on the ground plane of a rectangular patch antenna. The antenna design is suitable for wireless communication such as Wi-Fi and WLAN application. The antenna was simulated using Computer Simulation Technology (CST) software. The design was fabricated. This antenna operates at frequency of 2.45 GHz. A FR-4 substrate with relative permittivity of 4.3 was used in this design. The substrate and copper thickness is 1.6 mm and 0.035 mm, respectively. There are two types of antenna involved. The first antenna is a rectangular patch antenna without DGS which means the conventional antenna, and the other one is V-shape and circular ring defect on rectangular patch. The fabricated antenna was measured using vector network analyzer (VNA). The return loss of conventional antenna -16 dB has been improved to -26 dB on the V-shape and circular ring defect. A bandwidth was enhances 2 MHz. The size and shape of the slot affect the resonant frequency of antenna. The defected ground structure (DGS) of a microstrip line provides an additional effective inductive component, which enables a microstrip line to have a very high impedance to be realized hence shows a slow-wave characteristic.